1997
DOI: 10.2337/diacare.20.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders in Youths With IDDM: Rates and Risk Factors

Abstract: The results converge with findings from other studies, suggesting elevated psychiatric morbidity in contemporary samples of young people with IDDM. The morbidity partly reflects the high incidence of major depression in adolescence and generalized anxiety disorder in young adulthood. Monitoring the psychological status of young patients and their mothers may help to identify diabetic children at risk for psychiatric disorder and facilitate prevention or treatment efforts. Monitoring may be particularly benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
254
3
15

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(291 citation statements)
references
References 61 publications
19
254
3
15
Order By: Relevance
“…Up to 9.5% of the general population of adolescents are depressed, [8][9][10] and the rate is 2 to 3 times higher for adolescents with type 1 diabetes and other chronic health conditions. [11][12][13][14][15][16] When present, depression in adolescents with type 1 diabetes is associated with less frequent blood glucose monitoring (BGM), 17 higher HbA1c values, [18][19][20][21] and increased rates of diabetes-related hospitalizations. 22,23 All of these negative health outcomes are associated with higher risk of longterm complications from diabetes and consequent increase in medical care costs.…”
Section: Resultsmentioning
confidence: 99%
“…Up to 9.5% of the general population of adolescents are depressed, [8][9][10] and the rate is 2 to 3 times higher for adolescents with type 1 diabetes and other chronic health conditions. [11][12][13][14][15][16] When present, depression in adolescents with type 1 diabetes is associated with less frequent blood glucose monitoring (BGM), 17 higher HbA1c values, [18][19][20][21] and increased rates of diabetes-related hospitalizations. 22,23 All of these negative health outcomes are associated with higher risk of longterm complications from diabetes and consequent increase in medical care costs.…”
Section: Resultsmentioning
confidence: 99%
“…A longitudinal study by Kovacs et al [6] estimated that, after 10 years of follow up, psychiatric disorders had occurred among almost half of the patients at a mean age of 20 years and major depression had occurred in around a quarter. Few studies have related the prevalence of depression in type 1 diabetes to that in controls.…”
Section: Introductionmentioning
confidence: 99%
“…Those who are experiencing high depression are most likely to involve in endangered sexual practices and other behaviors. Depression that occurs during the age of late childhood will continue to adulthood in most of the cases; however, in certain cases, depressive disorders are diminished with the growing age (9,10). Another study has revealed, that 75% of the adults, who are experiencing Major depressive disorders (MDD) during their adult age, have experienced their first episode of depression during the age of childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Another study has revealed, that 75% of the adults, who are experiencing Major depressive disorders (MDD) during their adult age, have experienced their first episode of depression during the age of childhood. Furthermore, highly depressed adolescents and youth face the problem of communication among peers, and are most likely to be involved in physical fights with peers (1,11,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation